Seeds of change? Social practices of urban community seed sharing initiatives for just transitions to sustainability - Davies, Anna; Rut, Monika; Feeney, Jane K. (My University, 2022)
The sharing of seeds is a practice with ancient roots. However, the structures of global agri-food trade in late modernity have drastically reconfigured practices of exchange and reshaped matters of legal ownership, resulting in constrained access to seeds for many. Scholars and activists are increasingly concerned about the negative impacts these changes are having from a justice and sustainability perspective. To date, seed sharing research has predominantly occurred as one element of wider seed sovereignty debates, and particularly in relation to farmers in low- and middle-income countries. Seed sharing beyond these contexts has received limited attention. To broaden understanding of seed sharing and its diverse practices, this paper provides a foundational landscape level analysis of urban community seed sharing initiatives from 100 urban locations globally. It outlines the rules, tools, skills and understandings that shape seed sharing practices and teases out commonalities with, and differences between, these urban activities and those that currently dominate the landscape of seed sharing research. In conclusion, further research is proposed to build on these foundations and establish the contributions, actual and potential, that urban seed sharing provides for just transitions to more sustainable urban food systems.
PUBLISHED
Keywords: Seed sharing; Sustainability; Justice; Governance; Social practice theory; Smart & Sustainable Planet; SUSTAINABILITY; sustainability transitions; urban sustainability